Anti-religious divisions of Soviet State security bodies during inter-patriarchal period in the Russian Orthodox Church (1925-1943) - Pidhayko Volodymyr Heorhiyovych (Studia Humanitatis, 2020)
Based on rare published and unpublished sources this paper analyses the most famous group of agent files, agent-operative cultivations of special services implemented by state security agencies in relation to Church-monarchical and mystical groups. It shows main directions of the NKVD/NKGB activities on the “religious question” during the Great Patriotic War. In conclusion, partly under influence of state security agencies, Stalin moved from the oppression and restriction policy of the Russian Orthodox Church and other religious activities to the policy of a certain “détente”, which resulted in the revival of Orthodox parishes and communities of other faiths.